Layer‐by‐Layer Fabrication of Nanowire Sensitized Solar Cells: Geometry‐Independent Integration. (28th August 2014) - Acharya, Krishna P.; Ji, Zhiqiang; Holesinger, Terry G.; Crisp, Jeffrey A.; Ivanov, Sergei A.; Williams, Darrick J.; Casson, Joanna L.; Sykora, Milan; Hollingsworth, Jennifer A.
<x xml:space="preserve">Abstract</x> Thin film solar cells that are low in cost but still reasonably efficient comprise an important strategy for reaching price‐performance ratios competitive with fossil fuel electrical generation. Sensitized solar cells – most commonly dye but also semiconductor nanocrystal sensitized – are a thin film device option benefitting from lost cost material components and processing. Nanocrystal sensitized solar cells are predicted to outpace their dye‐based counterparts, but suffer from limited availability of approaches for integrating the nano‐sensitizers within a mesoporous oxide anode, which effectively limits the choice of sensitizer to those that are synthesized in situ or those that are easily incorporated into the oxide framework. The latter methods favor small, symmetric nanocrystals, while highly asymmetric semiconductors (e.g., nanowires, tetrapods, carbon nanotubes) have to date found limited utility in sensitized solar‐cell devices, despite their promise as efficient solar energy converters. Here, a new strategy for solar cell fabrication is demonstrated that is independent of sensitizer geometry. Nanocrystal‐sensitized solar cells are fabricated from either CdSe semiconductor quantum dots or nanowires with facile control over nanocrystal loading. Without substantial optimization and using low processing temperatures, efficiencies approaching 2% are demonstrated. Furthermore, the significance of a 'geometry‐independent' fabrication strategy is shown by revealing that nanowires afford important advantages compared to quantum dots as sensitizers. For equivalent nanocrystal masses and otherwise identical devices, nanowire devices yield higher power conversion efficiencies, resulting from both enhanced light harvesting efficiencies for all overlapping wavelengths and internal quantum efficiencies that are more than double those obtained for quantum dot devices.